Desalination Using Solar Evaporator - Mohd Zainul Ariffin Bin Abdul Hadi, Mohd Zainul Ariffin (2011)
This report discusses about Desalination Using Solar Evaporator process where the main objective of the project is to find the most promising process configuration which enable the process to produce an amount of 0.35m3 freshwater per hour and at the same time is feasible for low and middle income people to utilize it.